1999
DOI: 10.1111/j.1558-5646.1999.tb04524.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Induced Responses and Tolerance to Herbivory in Male and Female Fitness Components of Wild Radish

Abstract: Abstract.-Theory predicts that plant defensive traits are costly due to trade-offs between allocation to defense and growth and reproduction, Most previous studies of costs of plant defense focused on female fitness costs of constitutively expressed defenses. Consideration of alternative plant strategies, such as induced defenses and tolerance to herbivory, and multiple types of costs, including allocation to male reproductive function, may increase our ability to detect costs of plant defense against herbivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(119 citation statements)
references
References 93 publications
(139 reference statements)
0
113
0
5
Order By: Relevance
“…Although artificial and natural damage often have similar effects on plant performance [34], studies have also shown that not all plants respond similarly to artificial damage compared to damage caused by herbivores [37], [38]. This could for example be due to the lack of induced plants responses caused by herbivore saliva [39] or the timing of damage [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although artificial and natural damage often have similar effects on plant performance [34], studies have also shown that not all plants respond similarly to artificial damage compared to damage caused by herbivores [37], [38]. This could for example be due to the lack of induced plants responses caused by herbivore saliva [39] or the timing of damage [41].…”
Section: Discussionmentioning
confidence: 99%
“…Still, consumption of plant tissue by larvae may influence plants differently from damage by clipping [34], [37], [38]. For example prolonged exposure to larval saliva may trigger induced responses [39].…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have assessed tissue fitness value by removing different plant tissues and measuring the impact on subsequent plant fitness [6], [12]. However, although removal of needles without apparent defensive responses have been used elsewhere, we think that removal of plant tissues in pine trees could induce herbivory signaling and provoke defensive responses, potentially leading to dramatic changes in the plant sink-source balance, carbon allocation and growth patterns [32][34]. This is of particular relevance given that our aim is to study constitutive and induced defenses, and could well lead to confounding results.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies simulate damage mainly through manual clipping, which may be a poor surrogate for genuine herbivory (Strauss & Agrawal, 1999). In addition, little is known about how different kinds of herbivore damage influence tolerance to herbivory across naturally varying genotypes (but see Agrawal et al ., 1999; Tiffin & Rausher, 1999; Pilson, 2000). However, to understand the evolution of tolerance, it is essential to determine whether conspecific genotypes show differential tolerance to herbivore damage.…”
Section: Introductionmentioning
confidence: 99%